Solar ultraviolet radiation and CO2-induced ocean acidification interacts to influence the photosynthetic performance of the red tide alga Phaeocystis globosa (Prymnesiophyceae) - Chen, Shanwen; Gao, Kunshan; 高坤山 (2011)
National Basic Research Program of China [2009CB421207]; program for Changjiang Scholars and Innovative Research Team [IRT0941]; National Natural Science Foundation [40930846, 40876058] Future CO2-induced ocean acidification may interact with solar UV radiation to affect physiological performance of microalgae. Therefore, CO2/pH perturbation experiments were carried out under solar radiation with or without UV radiation (295-400 nm) to evaluate the combined effects of seawater acidification (pH 7.7 at 101.3 Pa CO2) and UV on Phaeocystis globosa that forms harmful algal blooms. Under high levels of solar radiation, the acidification reduced the growth rate and photochemical efficiency either under PAR alone or with the presence of UVR radiation. Under reduced levels of solar radiation (cloudy days), however, the CO2-enrichment and UVA acted synergistically to stimulate the photochemical yield and enhanced the growth rate. That is, the effects of CO2-induced acidification were reversed from the negative (sunny days) to positive (cloudy days). CO2 concentrating mechanism f P. globosa was not affected by the elevated pCO(2) in view of unchanged photosynthetic affinity for CO2 and stable activity of both intracellular and extracellular carbonic anhydrase. The increased acidity induced higher UVB-related photoinhibition of growth and non-photochemical quenching, and increased the dark respiration and the contents of Chl a, Chl c, and carotenoids, causing the cells to increase their energy demand against the combined stress. Overall, the findings imply that net or balanced effects of ocean acidification on phytoplankton would depend on the depth or mixing that alters the exposures of the cells in water columns to solar radiation.